Design strategies, results and evaluations of long-term chemical carcinogenesis studies. - Huff, J (Scandinavian Journal of Work, Environment & Health, 1992)
Long-term toxicology and chemical carcinogenesis experiments typically involve both sexes of two species of rodents divided randomly into sets of 50-60 animals per control and exposure groups. Ordinarily three exposure concentrations are gradated down from a top level likely to show some chemically associated toxicity, but which should not compromise the normal well-being or growth and survival patterns of the animals unduly. Duration of exposure is generally two years. Single, intermittent, or varied exposures are used to mimic specific occupational or environmental situations. Exposures are started prior to conception, during gestation and lactation, or at specified times thereafter. Extensive gross observations and microscopic pathology are performed on each animal, and incidences of neoplastic and nonneoplastic lesions are evaluated in age-adjusted statistical comparisons. The collated findings are then interpreted, evaluated, and presented for scientific peer review in public meetings, the aim being to identify qualitatively those environmental and occupational exposures that may likely induce cancer in humans.